An investigation of the wave energy resource on the South African Coast, focusing on the spatial distribution of the South West coast - Joubert, J. R. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2008.